Geotecnologias aplicadas no diagnóstico de qualidade de água para o abastecimento rural - Calderan, Sidival Antonio (2021)
This reaserch evaluate, in environmental terms, the springs, excavated wells and the deep tubular wells used for a source of access to drinking water in the São Matheus River hydrographic basin, in the city of Terra Boa – PR. For this, an application for mobile devices was developed, through the Appinventor™ platform (offered free of charge by Google™), for registration and collection records, which also allowed the storage of the geographic coordinates of the location. With the help of this application, water samples from springs, shallow wells and deep tubular wells were collected and recorded. Laboratory analyzes were performed for microbiological (Escherichia coli and total coliforms) and physicochemical (Iron, Zinc, Manganese elements and turbidity of watter) parameters of the collected samples. After laboratory processing and statistical examination of the data, the following results were reached: 1) Most samples collected in springs showed high levels of contamination by E. coli (75%) and total coliforms (75%); 2) excavated wells were contaminated in 80% of the cases analyzed; 3) Iron values above those indicated by Ministry of Health Port. 05/2017 were observed, especially in samples collected in deep tubular wells; 4) The values of the Fe and Zn analysis allowed to observe a clear distinction between the different types of sources. Finally, from the use of the GeoSai application, developed during the research, it was possible to draw up a anagement map, where the analyzes with parameters below the permitted were spatialized and correlated to a certain team of the Family Health Program, allowing greater speed in preventive measures such as guidelines and the delivery of disinfectant products.